The caste- and sex-specific DNA methylome of the termite Zootermopsis nevadensis - Glastad, Karl M. (Sci Rep, 2016)
Epigenetic inheritance plays an important role in mediating alternative phenotype in highly social species. In order to gain a greater understanding of epigenetic effects in societies, we investigated DNA methylation in the termite Zootermopsis nevadensis. Termites are the most ancient social insects, and developmentally distinct from highly-studied, hymenopteran social insects. We used replicated bisulfite-sequencing to investigate patterns of DNA methylation in both sexes and among castes of Z. nevadensis. We discovered that Z. nevadensis displayed some of the highest levels of DNA methylation found in insects. We also found strong differences in methylation between castes. Methylated genes tended to be uniformly and highly expressed demonstrating the antiquity of associations between intragenic methylation and gene expression. Differentially methylated genes were more likely to be alternatively spliced than not differentially methylated genes, and possessed considerable enrichment for development-associated functions. We further observed strong overrepresentation of multiple transcription factor binding sites and miRNA profiles associated with differential methylation, providing new insights into the possible function of DNA methylation. Overall, our results show that DNA methylation is widespread and associated with caste differences in termites. More generally, this study provides insights into the function of DNA methylation and the success of insect societies.